Biomimetic complexes‐graphene composites for redox processes. (24th January 2020) - Mahyari, Mojtaba; Hooshmand, Seyyed Emad; Sepahvand, Heshmatollah; Gavgani, Jaber Nasrollah; Hosseini, Seyed Ghorban
Abstract: Biomimetic complexes such as porphyrins, phthalocyanines, and hemins show promising catalytic activities in redox processes. Donor‐acceptor hybrids of these biomimetic macrocyclic complexes with graphene as one of the most critical allotropes of carbon are currently an outstanding scientific frontier. Notably, the composites that consist of these efficient and bio‐inspiring complexes anchored on the surface of the graphene and their widespread applications have gained ever‐increasing interest in the last decade, which expresses their efficiency in practice. Accordingly, this review covers the current status of biomimetic complexes‐graphene composites with particular emphasis on significant signs of their synthesis and characterization also highlighted applications of these composites in academia and industrial redox processes such as oxidation of organic compounds, epoxidation, oxygen reduction reactions, CO2 reduction, and hydrogen evolution reactions. Abstract : This review covers the current status of biomimetic complexes such as porphyrins, phthalocyanines, and hemins as well as graphene composites, particular emphasis on significant signs of their synthesis and characterization and highlighted applications of these composites in academia and industrial redox processes such as oxidation of organic compounds, epoxidation, oxygen reduction reactions, CO2 reduction, and hydrogen evolution reactions.